“Who is He? Who is my Main Hero?” The Principles of Constructing the Main Hero in l. Ulitskaya’s Novels - Сабо, Тюнде (Literatūra, 2017)
This study examines the principles that govern the construction of the main male hero in four ofL. Ulitskaya’s novels: The Kukotsky Enigma, Sincerely Yours, Shurik, Daniel Stein, Interpreter, and Jacob’s Ladder. The analysis shows that the principles of the construction of the heroes can be traced back to a source that precedes 19th century psychological prose. First, the characteristics of the four heroes can be explained with biographism; second, this can be done with Bakhtin’s idea of the construction of the “classic character.” Moreover, one of the characteristics of Ulitskaya’s novels is “multibiographism,” which, together with the “everyday perspectives” that appear in the biographies, leads to deheroization and the relativization of the main hero’s status.KAS JIS, MANO PAGRINDINIS HEROJUS?“ PAGRINDINIO HEROJAUS KONSTRAVIMO PRINCIPAI L. ULICKAJOS ROMANUOSEStraipsnyje nagrinėjami pagrindinių herojų – vyrų paveikslų konstravimo principai keturiuose Liudmilos Ulickajos romanuose: „Kukockio kazusas“, „Nuoširdžiai jūsų Šurikas“, „Danielis Štainas, vertėjas ir Jokūbo kopėčios“. Atlikta analizė rodo, kad tie principai gali būti kildinami iš ankstesnio šaltinio negu XIX a. proza. Herojų specifika aiškintina pirmiausia biografizmu ir „klasikinio charakterio“ kūrimo principais Michailo Bachtino koncepcijos kontekste. Be to, Ulickajos romanams būdingas „multibiografizmas“, kuris kartu su herojų biografijos buitine perspektyva suteikia pagrindiniam herojui reliatyvų statusą ir netgi herojus tą statusą praranda, t. y. deheroizuojamas.
Keywords: main male heros of L. Ulitskaya’s novels; biographism and multi-biographism; classic character; M. Bakhtin; deheroisation